Self-reflexivity in ethnography positioning an ambiguous ethnic identity - Gomez-Soluta, Andrea (Siliman Journal, 2009)
This paper presents the author's reflections on her own ethnic identity prompted by her ethnographic experiences while trying to study how the Igorot and Ifugao women constructed/reconstructed and negotiated or contested their ethnic identity. At the beginning of her fieldwork, it became necessary for her to answer the same questions - "Who am I?" and "What makes me an Igorot/Ifugao? - she posed to the study participants (to determine the cultural domains connected to their ethnic identity) because she entered each of the four research sites confidently positioning herself as an "ethnic insider". This position however became a methodological issue in her research when her interactions with the women participants made her realize the ambiguity of her ethnic identity. Consequently, she learned to negotiate her own ethnic self while attempting to understand the same process among the Igorot and Ifugao women as they inter-acted both with their in-group and out-group.